COVID-19 and citizen science: lessons learned from southern Africa. (2nd April 2020) - Rose, Sanjo; Suri, Jessleena; Brooks, Michael; Ryan, Peter G
Abstract : The COVID-19 lockdown has had a marked effect on citizen science projects, such as the Southern African Bird Atlas Project, SABAP2. With their mobility severely constrained, most citizen scientists in South Africa were not able to submit full protocol lists during the Alert Level 5 lockdown. There was a 70% decline in full protocol list submissions in April 2020, and only 20% of the number of pentads was surveyed, compared with the same period in the previous three years. The decline in ad hoc lists is also evident, with about a 50% decline in the number of lists submitted and 25% of the usual number of pentads. The number of citizen scientists submitting ad hoc lists only declined by about 15% in April, compared with previous years, indicating that volunteers were still eager to contribute to the atlas project, despite the challenging conditions. The BirdLasser 'Lockdown Challenge' further encouraged participation. Although the ability of citizen scientists to contribute full protocol lists to SABAP2 may have suffered, other projects with a scope more suited to lockdown thrived. The 'Lockdown Garden Surveys' instigated as part of a study of urban bird communities proved extremely successful, with 283 people regularly contributing point counts, many on a daily basis. The overwhelmingly positive response to initiatives like these indicates that the lockdown may have actually increased people's desire to participate in citizen science. The pandemic also has put the spotlight on nature within cities, encouraging people to take a fresh look at their surrounding greenspaces. The accompanying boom in citizen science and interest in nature is something that must be harnessed going forward, and we hope this can be sustained despite the harsh economic climate exacerbated by the pandemic.